2014
DOI: 10.1371/journal.pone.0106471
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gene Array Patterns in Dendritic Cells from Aged Humans

Abstract: Dendritic cells (DCs) are major antigen-presenting cells that play a key role in initiating and regulating innate and adaptive immune responses. DCs are critical mediators of tolerance and immunity. The functional properties of DCs decline with age. The purpose of this study was to define the age-associated molecular changes in DCs by gene array analysis using Affymatrix GeneChips. The expression levels of a total of 260 genes (1.8%) were significantly different (144 down-regulated and 116 upregulated) in mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…The increase in inflammatory response is not due to altered TLR expression as we have previously reported that the expression of TLRs is comparable between aged and young DCs [30]. This has been further confirmed with our gene array data on aged and young DCs [35]. The gene array data also did not show any difference in the expression of TSLPR, IL-33R, or ICOSL on aged DCs as compared to young DCs [35].…”
Section: Discussionsupporting
confidence: 91%
“…The increase in inflammatory response is not due to altered TLR expression as we have previously reported that the expression of TLRs is comparable between aged and young DCs [30]. This has been further confirmed with our gene array data on aged and young DCs [35]. The gene array data also did not show any difference in the expression of TSLPR, IL-33R, or ICOSL on aged DCs as compared to young DCs [35].…”
Section: Discussionsupporting
confidence: 91%
“…Ageing has a significant impact on DC functions [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Several reports suggest that phagocytosis, migration, and cytokine secretion are impaired in DCs isolated from aged individuals (60–90 years of age) compared to DCs from young individuals (20–40 years of age) [ 25 ].…”
Section: Age-associated Deterioration And/or Dysregulation Of Humamentioning
confidence: 99%
“…CD141 was chosen because CD141 + DCs are reported to be the human homolog of CD103 + DCs [ 25 ]. GARP was chosen because it was found to be significantly downregulated in DCs from aged compared to DCs from young subjects in our gene array data [ 26 ]. GARP expression has previously been reported on platelets and T regulatory cells where it plays an important role in tethering latent TGF-β on the surface [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%